Clocks in the clinic: circadian rhythms in health and disease. Issue 1117 (6th December 2018) - Kelly, Rachael M; Healy, Ultan; Sreenan, Seamus; McDermott, John H; Coogan, Andrew N
Abstract: Circadian rhythms are endogenously generated recurring patterns of around 24 hours with well-established roles in physiology and behaviour. These circadian clocks are important in both the aetiology and treatment of various psychiatric and metabolic diseases. To maintain physiological homeostasis and optimal functioning, living life synchronised to these clocks is desirable; modern society, however, promotes a '24/7' lifestyle where activity often occurs during the body's 'biological night', resulting in mistimed sleep and circadian misalignment. This circadian desynchrony can increase the risk of disease and can also influence treatment response. Clinicians should be aware of the influence that circadian desynchrony can have on health and disease, in order to potentially develop new therapeutic strategies and to incorporate chronotherapeutics into current treatment strategies to enhance their utility.